2016
DOI: 10.4137/jen.s40144
|View full text |Cite
|
Sign up to set email alerts
|

Toxico-Neurological Effects of Piroxicam in Monogastric Animals

Abstract: Piroxicam is a benzothiazine compound with anti-inflammatory, antipyretic, and analgesic properties. Because of the very high efficacy of piroxicam and its increasing use in the treatment of carcinomas in dogs and cats, there is a need for acute toxicity study of piroxicam in monogastric animals and its potential for causing secondary poisoning in puppies. Piroxicam manufactured by Shanxi Federal Pharmaceutical Co, Ltd. was used for this study. Revised up-and-down procedure was used for the estimation of media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Human equivalent dose (HED) formula was used to determine therapeutic dose of (5 mg/kg) piroxicam in WAD goats. 23,24 HED = animal dose × animal K m H k m whereas K m = Body surface area Body weight But human BSA = H 0.528 × W 0.528 × K. Goat BSA = BW 0.67 × 10 −3 . …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human equivalent dose (HED) formula was used to determine therapeutic dose of (5 mg/kg) piroxicam in WAD goats. 23,24 HED = animal dose × animal K m H k m whereas K m = Body surface area Body weight But human BSA = H 0.528 × W 0.528 × K. Goat BSA = BW 0.67 × 10 −3 . …”
Section: Methodsmentioning
confidence: 99%
“…Human equivalent dose (HED) formula was used to determine therapeutic dose of (5 mg/kg) piroxicam in WAD goats. 23,24 HED…”
Section: Drugs and Dosagementioning
confidence: 99%
“…In previous studies, the effective dose of piroxicam with analgesic effects in mice was determined to be 30 mg/kg. 14 Therefore, in the present study, two doses, 15 and 30 mg/ kg were used.…”
Section: Study Population (Animals)mentioning
confidence: 99%
“…At present, non-steroidal anti-inflammatory drugs (NSAIDs) and corticosteroids are widely used in the treatment of inflammatory diseases ( Lane et al, 2017 ). Research has revealed that NSAIDs have the advantage of fast onset of action and are more commonly used in clinical practice, but pharmacokinetic and pharmacodynamic tests have shown that these drugs have side effects such as gastrointestinal mucosal damage ( Saganuwan and Orinya, 2016 ). Therefore, the development of new anti-inflammatory treatments is imperative.…”
Section: Introductionmentioning
confidence: 99%